Dual inhibition of Src family kinases and Aurora kinases by SU6656 modulates CTGF (connective tissue growth factor) expression in an ERK-dependent manner - Cicha, Iwona; Zitzmann, Rita; Goppelt-Strübe, Margarete (International Journal of Biochemistry & Cell Biology, 2014)
Src kinases are regulators of the expression of connective tissue growth factor (CTGF/CCN2), which plays a role in fibrotic injuries. The aim of the present study was to evaluate the potential of SU6656, a dual inhibitor of Src family and Aurora kinases, to interfere with the synthesis of this pro-fibrotic factor. SU6656 impaired TGF-?-mediated upregulation of CTGF mRNA and protein in proximal epithelial HKC-8 cells, and also reduced CTGF expression in cells exposed to autocrine growth factors. In association with the inhibition of Src family kinases and diminished focal adhesion kinase activity, adherence of the cells was reduced. Furthermore, SU6656 interfered with Aurora kinase activity resulting in inhibition of cell division and formation multilobular nuclei after 24h. Comparable alterations were observed in primary tubular cells. When cell division was inhibited by SU6656 or ZM447439, a specific inhibitor of Aurora kinases, CTGF levels were back to control or even increased after 48h. The activity of RhoA-Rho kinase and ERK signaling was analyzed to delineate the signaling pathways responsible for the biphasic regulation of CTGF. While Rho kinase was not significantly altered by SU6656, ERK activity was inhibited in the early phase and increased after 24-48h. ERK activity correlated with secreted CTGF. As ZM447439 increased ERK activity only after 48h, cellular reorganization is likely responsible for triggering the ERK-dependent upregulation of CTGF. Taken together, in non-transformed epithelial cells, SU6656 modulates the expression of the pro-fibrotic factor CTGF in a time-dependent manner by inhibition of Src kinases and Aurora kinases.
EVALuna2:3674